Produção de sorgo forrageiro sob corte e pastejo - Gobetti, Suelen Tulio de Córdova (2010)
The study was conducted to evaluate different ways of using sorghum (Sorghum bicolor versus Sorghum sudanensis) system for use in cutting and / or grazing, supplemented with 0 and 1% by weight of live lambs. The experimental design was complete block design with three replications, and comparisons of means by Tukey test at 5%. There was no interaction (P <0.05) between system use and supplementation for all parameters. In the analysis of forage system using grazing had greater involvement of unwanted plants in sward structure (milhã e papuã) and use system cut the best combination of MS of pasture, stalks and leaves, compared to other treatments. In the analysis of animal weight gain, the method was more efficient and higher weight gain were observed in the supplementation of 1% of body weight, regardless of the usage adopted. The use of sorghum in diets for sheep grazing, with or without supplementation is suitable for the weight gain of lambs.